Preliminary feasibility and clinical utility of the Unified Protocol for the transdiagnostic treatment of emotional disorders in people with long COVID-19 condition: A single case pilot study - Verónica Martínez-Borba; Óscar Peris-Baquero; Iván Prieto-Rollán; Jorge Osma; Esther del Corral-Beamonte (PLoS ONE, 2025)
Purpose The implementation of psychological interventions in long COVID-19 patients is still very limited. This study aims to analyze the feasibility and preliminary utility of the Unified Protocol (UP), for the psychological treatment of emotional disorders in long COVID-19 patients. Methods 12 long COVID-19 patients (mean age = 47.92; SD = 13.18) presenting emotional disorders/symptoms received the UP through 8 online sessions. Results All participants completed the UP psychological program, attending all eight sessions and the 6-month follow-up appointment. However, adherence to the assessment protocol was lower, with a 33% dropout rate at the 6-month follow-up. High satisfaction was reported with both the UP program (mean = 9.75) and the online format. Satisfaction with individual UP modules ranged from 7.17 to 9 points (from 0 = any satisfaction to 10 = highest satisfaction). Qualitative feedback emphasized the usefulness of the UP program, with some participants suggesting additional contents (i.e., training in assertive communication skills), more personalized modules (i.e., providing just some UP modules) or increasing the number of sessions. In terms of the UP clinical utility, 25 mental clinical diagnoses were established at pre-assessment; 50% of participants no longer met criteria for a mental clinical diagnosis at post-assessment, increasing to 67% at follow-up. Most therapeutic objectives were achieved or initiated over the course of the intervention (78% at post-assessment; 86% at follow-up). At post-assessment significant improvements were observed in anxiety (8 participants), depression (9 participants), emotion dysregulation (4 participants) and quality of life scores (7 participants), although 2 participants did not maintain these gains in emotion regulation and quality of life at follow-up. Conclusion The promising results of the UP in terms of high participant satisfaction and clinical improvements in anxiety and depression scores suggest that the UP could be a valuable psychological intervention for individuals with long COVID-19 and comorbid emotional disorders. The modest improvements found in other outcomes highlighted the need to better adapt the psychological interventions for long COVID-19 patients.